Genome-wide investigation of WRKY gene family in Lavandula angustifolia and potential role of LaWRKY57 and LaWRKY75 in the regulation of terpenoid biosynthesis - Kelimujiang, Kelaremu; Zhang, Wenying; Zhang, Xiaxia; Waili, Aliya; Tang, Xinyue; Chen, Yongkun; Chen, Lingna (Frontiers in Plant Science, 2024)
The WRKY transcription factors are integral to plant biology, serving essential functions in growth, development, stress responses, and the control of secondary metabolism. Through the use of bioinformatics techniques, this research has effectively characterized 207 members of the WRKY family (LaWRKY) present in the entire genome of Lavandula angustifolia. Phylogenetic analysis classified LaWRKYs into three distinct categories based on conserved domains. Collinearity analysis revealed tandem repeats, segmental duplications, and whole genome duplications in LaWRKYs, especially for segmental duplication playing a significant role in gene family expansion.LaWRKYs displayed distinct tissue-specific expression profiles across six different tissues of L. angustifolia. Particularly noteworthy were 12 genes exhibiting high expression in flower buds and calyx, the primary sites of volatile terpenoid production, indicating their potential role in terpenoid biosynthesis in L. angustifolia. RT-qPCR analysis revealed a notable increase in the expression levels of most examined LaWRKY genes in flower buds in response to both intense light and lowtemperature conditions, whereas the majority of these genes in leaves were primarily induced by drought stress. However, all genes exhibited downregulation following GA treatment in both flower buds and leaves. Overexpression of LaWRKY57 (La13G01665) and LaWRKY75 (La16G00030) in tobacco led to a reduction in the density of glandular trichomes on leaf surfaces, resulting in changes to the volatile terpenoid composition in the leaves. Specifically, the content of Neophytadiene was significantly elevated compared to wild-type tobacco, while compounds such as eucalyptol, cis-3- Hexenyl iso-butyrate, and D-Limonene were produced, which were absent in the wild type. These findings provide a valuable reference for future investigations into the biological functions of the WRKY gene family in L. angustifolia.